2018
DOI: 10.1016/j.jadohealth.2017.11.304
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Partner and Nonpartner Violence Among High-Risk Youth

Abstract: Implications for prevention are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(39 reference statements)
3
1
0
3
Order By: Relevance
“…The peer and dating aggression subgroup also followed an unexpected pattern in that individuals in this group were characterized by relatively low stable involvement in heavy alcohol use and nonviolent delinquency concomitant with fairly high, stable risk of involvement in dating aggression and high initial risk for involvement in peer aggression that declined over time but remained higher than that of the declining peer aggression group. While this pattern was not predicted by Moffitt's theory, the finding of a subgroup characterized by a high likelihood of engaging in aggression toward peers and dating partners is consistent with previous studies examining cross-contextual aggression patterns (e.g., Garthe et al, 2018;Heinze et al, 2018;Reyes, Foshee, Markiewitz, et al, 2018. The fact that aggression risk in this subgroup did not track together with risk for nonviolent delinquency or alcohol use was surprising, however, and suggests there may be unique factors influencing the propensity to engage in physical aggression that may differ from those influencing risk for other problem behaviors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The peer and dating aggression subgroup also followed an unexpected pattern in that individuals in this group were characterized by relatively low stable involvement in heavy alcohol use and nonviolent delinquency concomitant with fairly high, stable risk of involvement in dating aggression and high initial risk for involvement in peer aggression that declined over time but remained higher than that of the declining peer aggression group. While this pattern was not predicted by Moffitt's theory, the finding of a subgroup characterized by a high likelihood of engaging in aggression toward peers and dating partners is consistent with previous studies examining cross-contextual aggression patterns (e.g., Garthe et al, 2018;Heinze et al, 2018;Reyes, Foshee, Markiewitz, et al, 2018. The fact that aggression risk in this subgroup did not track together with risk for nonviolent delinquency or alcohol use was surprising, however, and suggests there may be unique factors influencing the propensity to engage in physical aggression that may differ from those influencing risk for other problem behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…Along these lines, an unexpected finding was that that girls (vs. boys) and Black (vs. White) youth were significantly less likely to belong to the multidomain high-risk group than to the other risky behavior patterns (PDAG and DPA) and were significantly more likely to belong to the peer and dating aggressor group compared with all of the other patterns identified. The latter finding is consistent with some previous cross-sectional research (Heinze et al, 2018;Whiteside et al, 2013). For example, Heinze et al (2018) conducted a study examining partner and nonpartner violence perpetration in a sample of high-risk young adults and found that, relative to those in the nonviolent group, youth involved in both partner and nonpartner violence perpetration were more likely to be female than male and to be African American than non-African American.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…La hipótesis 2, referida a la relación directa y positiva entre los problemas de adaptación y la victimización de violencia de pareja en mujeres, fue parcialmente confirmada debido a que se encontró una mayor victimización en el sexo femenino probablemente en respuesta a un aprendizaje por observación de modelos de violencia de pareja (Forkea et al, 2018;Heinze et al, 2018;Shorey et al, 2018). Por otro lado, el desajuste personal y clínico no se asociaron con victimización, mientras que el desajuste escolar y los síntomas emocionales mostraron una correlación con la victimización.…”
Section: Discussionunclassified
“…violencia, adolescencia, noviazgo, victimización, adaptación La violencia de pareja ha sido un problema frecuentemente abordado en diferentes estudios dada su alta prevalencia e incidencia (Heinze et al, 2018;Mohammad-Alizadeh-Charandabi, Bahrami-vazir, Kamalifard & Mirghafourvand, 2016;Wincentak, Connolly & Card, 2017); sin embargo, las investigaciones en adolescentes relacionadas con problemas de adaptación, agresión y victimización de la violencia de pareja no han sido suficientes, particularmente en el contexto colombiano.…”
Section: Palabras Claveunclassified